Differential H. pylori-Induced MAPK Responses Regulate Lewis Antigen Expression and Colonization Density on Gastric Epithelial Cells Between Children and Adults - Yang, Yao-Jong; Lu, Chia-Ling; Sheu, Bor-Shyang (Frontiers in Immunology, 2022)
Helicobacter pylori causes gastrointestinal diseases, the manifestations of diseases are more serious in adults than in children. Lewis antigen expressions on the gastric epithelium serves as receptors targeted by H. pylori. Moreover, the MAPK signaling pathway involves glycoprotein synthesis of Lewis antigens. We aimed to investigate whether differences in H. pylori-induced MAPK responses mediate gastric Lewis antigens expression and colonization density differently in children and adults. We used human stomach fetal epithelium (HSFE) and SV40-immortalized human normal gastric epithelial (GES-1) cell lines to mimic primary gastric epithelium of children and adults, respectively. H. pylori colonization intensity and Lewis antigens were significantly higher in GES-1 than in HSFE cells, whereas IL-8 and IL-6 levels were significantly higher in HSFE than in GES-1 cells after infection. c-Jun N-terminal kinase (JNK) siRNA and inhibitor (SP600125) experiments showed that Lewis antigen expression and H. pylori colonization were reduced in GES-1 cells but increased in HSFE cells. Furthermore, p-p38 intensity was significantly higher in the superficial epithelium of the children than in the adults with/without H. pylori infection. The overexpression of p38 in GES-1 cells downregulated H. pylori-induced JNK activity mimicking H. pylori infection in children. In conclusion, a higher p38 expression in gastric epithelium counteracting JNK activity in children may contribute to lower Lewis antigen expression and colonization density than in adults after H. pylori infection.